2021
DOI: 10.1101/2021.12.08.471664
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combinatorial mRNA vaccination enhances protection against SARS-CoV-2 delta variant

Abstract: Emergence of SARS-CoV-2 variants of concern (VOC), including the highly transmissible delta strain, has posed challenges to current COVID-19 vaccines that principally target the viral spike protein (S). Here, we report a nucleoside-modified mRNA vaccine that expresses the more conserved viral nucleoprotein (mRNA-N). We show that mRNA-N alone was able to induce a modest but significant control of SARS-CoV-2 in mice and hamsters. Critically, by combining mRNA-N with the clinically approved S-expressing mRNA vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
2
1
0
Order By: Relevance
“…The S + N group showed increased S protein-specific cellular immunity levels after three immunizations. One SARS-CoV-2 mRNA vaccine study reported that combinatorial S + N induced an augmented S-specific CD8+ T-cell response compared with S alone, which is consistent with our results [ 24 ]. Another study reported that T-cell responses to S and N antigens after dual-antigen hAd5 S + N prime vaccination alone were equivalent to those from previously SARS-CoV-2-infected patients, and in silico prediction models of T-cell epitope HLA binding suggested that T-cell responses to the hAd5 S + N vaccine will retain their efficacy against the B.1.351 variant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The S + N group showed increased S protein-specific cellular immunity levels after three immunizations. One SARS-CoV-2 mRNA vaccine study reported that combinatorial S + N induced an augmented S-specific CD8+ T-cell response compared with S alone, which is consistent with our results [ 24 ]. Another study reported that T-cell responses to S and N antigens after dual-antigen hAd5 S + N prime vaccination alone were equivalent to those from previously SARS-CoV-2-infected patients, and in silico prediction models of T-cell epitope HLA binding suggested that T-cell responses to the hAd5 S + N vaccine will retain their efficacy against the B.1.351 variant.…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, the reduction in virus titers cannot be specifically attributed to the M or N protein, and nAb levels were not evaluated in this study. One SARS-CoV-2 mRNA vaccine study reported that S + N co-immunization induced an augmented S-specific CD8+ T-cell response and neutralizing antibodies activity, providing better protection in the lungs against the Delta variant compared with S alone, which is consistent with the results of this study [ 24 ]. Another study reported that the N protein of transmissible gastroenteritis coronavirus promoted the synthesis of neutralizing antibodies when porcine TGEV-IMMUNE cells were stimulated with a combination of S and N proteins in vitro, and this effect might be explained by the helper T-lymphocyte response to the N protein [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
“…Even COVID-19 infection demonstrated that T cell response is important to generate memory response and lower severity in infected patients (14,15,16,17). Other studies concluded that nucleocapsid protein has to be included in further vaccine strategy (18,19,20,21). This can be a promising strategy to curb circulating Delta (22), Omicron variants (23) and hybrids (24) simultaneously.…”
Section: Introductionmentioning
confidence: 99%